Herramientas del marketing utilizadas en tiempo de confinamiento en las empresas distribuidoras de alimentos balanceados del cantón Mejía, parroquia Santiago Apóstol de Machachi, periodo abril- agosto 2020. - Lluman Aguilar, Evelyn Karina (2021)
The current problematic situation regarding the use of digital marketing tools of feed traders in the parish of Machachi, is generated mainly due to the limited knowledge they have about them; therefore, in this work we proposed as a general objective to diagnose the digital marketing tools used in feed distributors in the Canton Mejia, parish Santiago Apostle of Machachi, period April-August 2020. and as specific objectives to make the theoretical foundation, collect primary and secondary information, to design a proposal with these data on the use of digital tools applicable in the marketing of balanced food, research carried out in the line of management and economics for human and social development; The methodological design was carried out, identifying the target population of 25 marketers belonging to the urban area of Machachi, using the deductive method, the survey technique and a questionnaire as an instrument, then the data were tabulated and analyzed, with this analysis a proposal was developed for the use of digital tools to enhance the competitiveness of marketing companies of balanced feed and analyze the benefits of its use today.